The use of a model sand filtration system for greywater treatment: a case study of hotels and hostels in Eastern Region, Ghana - Anim Ofosu, Samuel; Okoh Agyemang, Emmanuel; Wiafe, Samuel (Health, Safety and Environment, 2020)
The research aimed at assessing the performance of a model sand filtration system for the treatment of greywater generated by the Hotels and Hostels in Ghana. Fifteen (15) water quality parameters were analyzed by collecting influent and effluent wastewater samples of the model sand filtration system and their average values compared with EPA (Ghana) guidelines for wastewater discharges into the environment. Most of the effluent wastewater pollutant met the set guidelines, while others were unacceptable. The ability of the model sand filtration system to effectively deal with key pollutants such as Colour 81%, BOD 74%, COD 70%, Turbidity 65% suggest that the model sand filter is efficient. The use of the model sand filter will not only lead to wastewater treatment before final discharge into the environment but also promote environmentally sustainable development of the country.